2021
DOI: 10.1155/2021/6668175
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillations Facilitate Effective Learning in Excitatory-Inhibitory Balanced Neural Circuits

Abstract: Gamma oscillation in neural circuits is believed to associate with effective learning in the brain, while the underlying mechanism is unclear. This paper aims to study how spike-timing-dependent plasticity (STDP), a typical mechanism of learning, with its interaction with gamma oscillation in neural circuits, shapes the network dynamics properties and the network structure formation. We study an excitatory-inhibitory (E-I) integrate-and-fire neuronal network with triplet STDP, heterosynaptic plasticity, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 70 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Indeed, it has been shown that E-I balanced networks with critical features found here (e.g., gamma oscillation and weak pairwise correlation) can achieve most efficient coding [65]. Such dynamic features are also beneficial to encode memory in networks through spike-timing-dependent plasticity [83].…”
Section: Neural Oscillation and Criticalitymentioning
confidence: 65%
“…Indeed, it has been shown that E-I balanced networks with critical features found here (e.g., gamma oscillation and weak pairwise correlation) can achieve most efficient coding [65]. Such dynamic features are also beneficial to encode memory in networks through spike-timing-dependent plasticity [83].…”
Section: Neural Oscillation and Criticalitymentioning
confidence: 65%
“…Gamma oscillations orchestrate activity synchronization across brain regions [10, 11], aiding memory retrieval [10, 11]. They align with the time constant of spike-timing-dependent plasticity (STDP) [45, 46], facilitating more effective synaptic modification, especially in the occurrence of spike-gamma coherence [16, 47]. These properties instantiate their importance in memory formation as well as the formation of cognitive maps, indicating the significance of gamma oscillations in encoding spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the variability (CV) of the model is slightly larger than that observed in LFP; the broad peak in ERP and firing rate from monkey LFP do not exactly match in timing; the frequencies of Alpha oscillation in human EEG and monkey LFP do not match. Future studies can use such E–I balanced network as a core model with additional biological details to study more specific information processing associated to the multiple neural response features to external stimulus, such as learning and memory (Li et al 2021b ; Li et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%